Cervical expression of elafin and secretory leukocyte peptidase inhibitor does not predict preterm delivery in twin pregnancy – results from a pilot study (Journal of Medical Science, 2021)
Background. Elafin and secretory leukocyte peptidase inhibitor may serve as the predictors of cervical shortening and preterm delivery in twin gestation. Material and Methods. A prospective observational study was conducted between September 2016 and March 2017. Cervicovaginal swabs collected from 40 women with twin gestation were analysed and the mRNA expression of elafin and secretory leukocyte peptidase inhibitor (SLPI) correlated with preterm delivery. Results. The mean gestational age at delivery was 35.6 ± 5.8 weeks, with 23 women delivering before 37 weeks (57.5%), 7 before 34 weeks (17.5%) and 3 before 32 weeks of gestation (7.5%). The mRNA expression of elafin and SLPI was not dependent on chorionicity and did not correlate with gestational age at delivery. Conclusions. Elafin and SLPI are not appropriate predictors of preterm delivery in twins.